2013
DOI: 10.1182/blood.v122.21.5149.5149
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation Of The Novel, Orally Bioavailable Selective Inhibitor Of Nuclear Export (SINE) Verdinexor (KPT-335) In Spontaneous Canine Cancer: Results Of Phase I and Phase II Clinical Trials

Abstract: SINE (Selective Inhibitors of Nuclear Export) block the activity of XPO1/CRM1, 1 of 7 nuclear export proteins in cells, forcing the nuclear retention of key tumor suppressor proteins (TSP), leading to selective apoptosis of tumor cells.  The purpose of these studies was to evaluate the in vitro activity of SINE against canine tumor cell lines and investigate the biological activity of Verdinexor (KPT-335) in dogs with spontaneous cancers as proof of principle for human clinical studies with SINE. Several diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…[21] In a subsequent phase 2 trial of verdinexor for canine lymphoma, objective responses (PR or CR) were noted in 20 of 58 (34%) treated animals. [22] Selinexor is currently in early phase clinical trials in both adult and pediatric malignancies. Phase 1 testing in adults evaluated either twice or thrice weekly dosing, with single agent phase 2 evaluations going forward primarily using the twice-weekly schedule.…”
Section: Introductionmentioning
confidence: 99%
“…[21] In a subsequent phase 2 trial of verdinexor for canine lymphoma, objective responses (PR or CR) were noted in 20 of 58 (34%) treated animals. [22] Selinexor is currently in early phase clinical trials in both adult and pediatric malignancies. Phase 1 testing in adults evaluated either twice or thrice weekly dosing, with single agent phase 2 evaluations going forward primarily using the twice-weekly schedule.…”
Section: Introductionmentioning
confidence: 99%
“…KPT-185 was the lead compound designed primarily for in vitro studies, and its orally bioavailable analog, KPT 251 has been successfully shown to have preclinical efficacy against various haematological and solid cancers in mice models 19 . KPT-335 was the first chemotherapeutic agent approved for treatment of canine lymphoma 23 , 56 . Both KPT-335 and KPT-185 were almost equally effective at disrupting XPO1-mediated export (1.5 µM).…”
Section: Discussionmentioning
confidence: 99%
“…Both pathways are subverted or manipulated during RSV infection and likely have a direct effect on RSV replication 58 , 59 . Treatment with SINE compounds could impact downstream pathways regulated by XPO1 and have been shown to cause cell cycle arrest, increase in inflammation and apoptosis in cancer cells 14 , 56 , 60 62 . RSV causes cell cycle arrest of the host cells in the S phase probably to promote its replication 63 , 64 .…”
Section: Discussionmentioning
confidence: 99%